THE DETERMINANTS OF CURRENCY EUROIZATION IN THE BALKANS - Anes Kadić; Abdul Wahab Aidoo; Ognjen Riđić (Economic Review)
The study aims to explore the euroization phenomenon in the Balkans, or more precisely, the main determinants of currency euroization in the selected seven Balkan countries (Albania, Bosnia and Herzegovina, Bulgaria, Croatia, North Macedonia, Romania, and Serbia) between 2000 and 2019. Currency euroization is proxied by two variables: foreign currency deposits and foreign currency denominated liabilities to total liabilities. This study has altogether showed that the rates of deposit and liabilities euroization had stayed persistent over a period of 20 years, with very small variations, even during the period of the 2008 crisis and its aftermath. The results of panel data analysis have showed that deposit euroization is influenced by consumer price index, real interest rate and trade openness. For liability euroization, trade openness and real effective exchange rate have proved to be statically significant variables, but with negative and positive effect respectively.